EP.TU.440Managements of blood thinning medications in elderly populations presenting with rectal bleeding: Are we doing it right?. (28th October 2021) - Prasannakumar, A Bavikatte; Uwaoma, S; Zahid, M; Herath, D; Olugbemi, M; Sebastian, B
Abstract: Purpose: Rectal bleeding is a common adverse effect of blood thinners in elderly patients resulting in admission. Our aim is to review the management of bold thinning medications in populations. Methods: A retrospective analysis of patients admitted with per-rectal bleed from 2018 to December 2020 was performed. All patients above the age of 60 years on blood-thinning medications were analyzed in terms of management and discharge. Results: A total of 93 (54.71%) patients out of 170 were included in the study. The median age was 83 years. The majority of them were on Direct Oral-Anticoagulants (DOAC) (35.4%), Clopidogrel (26.8%) and Aspirin (32.5%) with remaining on warfarin (14%) and dual anti-platelets (3.2%). On admission DOAC and warfarin was stopped in all the patients and antiplatelets was stopped in 76% of them. Identical percentage of patients in all the groups required blood transfusion. At discharge, DOAC was restarted in 33% of the patients with similar percentage discontinued. 6% were switched to alternative and the rest were due to outpatient review. Warfarin and antiplatelets was restarted in 61% and 62% of the patients respectively. Alternative medications were initiated on 7.6% of patients on warfarin and 5.4% on antiplatelets. Readmissions were mainly seen in patients on antiplatelets (10%). No patients in the study developed thrombotic complications. Conclusion: Individual patient circumstances lead to variations in the management of blood thinning medications with per-rectal bleed. Larger trials are needed to ensure uniformity. Readmissions were mostly seen in patients on antiplatelets.